Science and Culture: Inheritance Process through Education and History - Khaeruddin, Khaeruddin; Al Fiqri, Yanuar (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This article discusses the role of Education and History as a medium for the transmission of knowledge and culture. In simple terms, everything that is known is called knowledge, and all knowledge that is compiled based on scientific principles is called science. Culture can be defined as the result of creation, work and human taste which also includes science. Science can be understood as a set or collection of knowledge that is organized and has systematic procedures and has scientific steps. Science gives birth to and supports the creation of culture, and then this culture develops and preserves that knowledge. In the process of inheritance or preservation of culture and knowledge, this is where the role of history as a science and education as a system. History as a science which is a record of events that occurred in the past that has distinctive value and has a broad impact on society, history becomes a science that